Meningkatkan Minat Beli Ulang Konsumen Terhadap Produk Kerajinan dan Kesenian - Janiawati, Ni Kadek; Sugianingrat, I.A.P Widani; Astrama, I Made (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
The tight competition causes every company, including those engaged in crafts and arts, to experience a decline in sales turnover as experienced by CV. Novita in Gianyar Regency. Repurchase intention can be influenced by the quality of the product offered and also the satisfaction caused by the quality of the product. The purpose of this study was to determine the effect of product quality on repurchase intention directly and through mediation of consumer satisfaction. The research subjects are CV customers. Novita as many as 112 customers with purposive sampling method. Primary data that has been collected using a questionnaire using a five-choice Likert Scale then tested for validity and reliability, then continued with path analysis test and Sobel test to answer the hypothesis. The results of the study prove that product quality has a positive and significant effect on repurchase intention and customer satisfaction, satisfaction has a significant positive effect on repurchase interest, and satisfaction mediates the effect of product quality on repurchase interest